The 're-norming' of working from home during COVID-19: A transtheoretical behaviour change model of a major unplanned disruption. (October 2022) - Delbosc, Alexa; Currie, Graham; Jain, Taru; Aston, Laura
Abstract: Significant disruptive events have the potential to change travel behaviour in the long-term. COVID-19 has caused the most significant disruption of travel behaviour in living memory. One of the most notable changes has been the increase in working from home, which was forced upon many workers during lockdowns and 'stay at home' orders. But much is still unknown about the long-term impacts of those changes. This study explores the influence of the COVID-19 pandemic on changing work from behaviours using the Transtheoretical Model of behaviour change. The Transtheoretical Model has been widely used to study behaviour change in health, with some application to travel behaviour change. In this paper, we explore whether people's 'stage of change' before COVID-19 has an impact on their long-term intent to work from home. We found that only 12% of respondents had considered working from home more before COVID, yet those that had were far more likely to intend to work from home in the long term. In addition, we unpack the influence of 'process of change' factors, some of which point to a potential 're-norming' of attitudes toward working from home. Although self-efficacy (feeling capable to work from home) was an important factor, it was not as important as the attitudes of employers and colleagues toward working from home. Implications of the findings for research and practice are explored. Highlights: Transtheoretical Model explains intent to work from home (WFH) more 'after COVID'. Most people (79%) hadn't considered increasing WFH before COVID. Contemplating/preparing for change increases intent to WFH more 'after COVID'. Process of change factors (helping relationships, social liberation) increase intent to WFH. External constraints were more important than individual desire to WFH.